2022
DOI: 10.48550/arxiv.2210.16642
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Unifying the Discrete and Continuous Emotion labels for Speech Emotion Recognition

Abstract: Traditionally, in paralinguistic analysis for emotion detection from speech, emotions have been identified with discrete or dimensional (continuous-valued) labels. Accordingly, models that have been proposed for emotion detection use one or the other of these label types. However, psychologists like Russell and Plutchik have proposed theories and models that unite these views, maintaining that these representations have shared and complementary information. This paper is an attempt to validate these viewpoints… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Although this study has shown the limitation of this approach with a state-of-the-art classifier/regressor, the benefits from dimensional annotation for classification are not new in the literature. For example, [18]- [20] suggested employing both annotations in a multitask approach to improve classification results. Although these studies showed that dimensional information can be helpful for classification, our study has indicated the power of only dimensional information in the combined paradigm.…”
Section: Discussionmentioning
confidence: 99%
“…Although this study has shown the limitation of this approach with a state-of-the-art classifier/regressor, the benefits from dimensional annotation for classification are not new in the literature. For example, [18]- [20] suggested employing both annotations in a multitask approach to improve classification results. Although these studies showed that dimensional information can be helpful for classification, our study has indicated the power of only dimensional information in the combined paradigm.…”
Section: Discussionmentioning
confidence: 99%